THE AESTHETICS AND ETHICS OF SHARAF RASHIDOV'S JOURNALISTIC STYLE: A PHILOLOGICAL READING AND METHODOLOGICAL NOTES OF A LANGUAGE EDUCATOR - Suyarova Aynur Ibodullaevna (International Journal of Literature and Language Studies, 2026)
This paper examines the journalistic legacy of Sharaf Rashidov through the lens of aesthetic and ethical categories. Within the framework of comparative literary studies, contrastive linguistics, and translation studies, it provides a detailed analysis of the author's style, in which the traditions of classical Eastern literature and contemporary humanistic ideas are organically synthesized. Special attention is given to the linguoculturological dimensions of the texts; the paper investigates the functioning of national realia in Rashidov's journalism and novels — including The Mighty Wave, Stronger Than the Storm, and The Victors — as well as the mechanisms by which these elements are adequately conveyed and interpreted in a foreign-language environment.